Dynamic Response and Robustness Evaluation of Cable-Supported Arch Bridges Subjected to Cable Breaking - Guotao Shao; Hui Jin; Ruinian Jiang; Yue Xu (Shock and Vibration)
Cable-supported arch bridges have had many cable break accidents, which led to dramatic deck damage and even progressive collapse. To investigate the dynamic response and robustness of cable-supported arch bridges subjected to cable breaking, numerical simulation methods were developed, compared, and analyzed, and an effective and accurate simulation method was presented. Then, the cable fracture of a prototype bridge was simulated, and the dynamic response of the cable system, deck, and arch rib was illustrated. Finally, the robustness evaluation indexes of the cable system, deck, and arch rib were constructed, and their robustness was evaluated. The results show that the dynamic response of the adjacent cables is proportional to the length of the broken cable, while the dynamic response of the deck is inversely proportional to the length of the broken cable. The dynamic amplification factor of the cable tension and deck displacement is within 2.0, while that of the arch rib bending moment exceeds 2.0. The break of a single cable will not trigger progressive collapse. When subjected to cable breaking, the deck system has the least robustness. The proposed cable break simulation procedure and the robustness evaluation method are applicable to both existing and new cable-supported bridges.